Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae) - Souma, Jun (Zootaxa, 2020)
Two lace bug genera, Baeochila Drake & Poor, 1937 and Idiocysta China, 1930 (Hemiptera: Heteroptera: Tingidae) are recorded from Japan for the first time, and two new species, B. horvathi sp. nov. and I. takarai sp. nov., are described. The former was collected from the vines of Hedera rhombea (Miq.) Bean (Araliaceae) and the bark of Trachycarpus fortunei (Hook.) H.Wendl. (Arecaceae) in suburbanized areas of Honshu, Shikoku and Kyushu, and the latter was collected from the leaves of Freycinetia formosana Hemsl. (Pandanaceae) in the laurilignosa ecosystem of the Ryukyu Islands. The distribution ranges and host plant relationships of the two new species are discussed. Keys to all species of the two genera and photographs of living individuals for the new species are also presented.